COMPARISON OF HOUSEHOLDS" EXPENDITURES STRUCTURES IN SELECTED COUNTRIES OF EUROPEAN UNION - Dudek, Hanna; Koszela, Grzegorz (Acta Scientiarum Polonorum. Oeconomia, 2013)
The article discusses the problem of similarities and differences of countries with respect to the structure of household expenditure in the European Union. This issue is important due to problem of economic and social and cohesion among member states. Comparative analysis of structures of consumption expenditures of households in EU member countries is performed using distance measure approach taking into account relative differences. For this purpose measure known in Polish language literature as Nowak's measure is applied. Background for analysis is data collected from national sources by the Statistical Office of the European Communities (Eurostat). Using quantitative analysis countries with similar to Poland structures of consumer expenditures are identified.